Comparative Analysis and the Influence of Science Process Skills on Students' Digital Literacy on Measurement Materials - Astalini, Astalini; Darmaji, Darmaji; Kurniawan, Dwi Agus; Azzahra, Miftahul Zannah (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
This research aims to determine the comparison and influence of students' science process skills on students' digital literacy in measurement material. This research uses a quantitative type of research with an explanatory approach. The sampling technique used was purposive sampling with a sample size of 60 students. Data collection techniques in this research included observation sheets and questionnaires. The data analysis technique in this research uses descriptive statistical methods and inferential statistics. Based on the independent sample t-test results for science process skills and digital literacy of Al-Falah High School students in Jambi City, a Sig. (2-tailed) value less than 0.05 was obtained.. Thus, it can be concluded that there are differences in science process skills and critical thinking skills between students in classes X A and X B. According to the results of a simple linear regression test to see the effect of science process skills on students' digital literacy at Al-Falah High School in Jambi City, it can be concluded that for class X A, science process skills affect students' digital literacy, with an R Square value of 0.46, meaning that 46% of science process skills influence students' digital literacy. For class X B, science process skills also affect students' digital literacy, with an R Square value of 0.42, meaning that 42% of science process skills influence students' digital literacy. Based on hypothesis testing, it is known that there are differences in science process skills and digital literacy between students in classes X A and X B. In addition, students' science process skills influence digital literacy in measurement material.